Peningkatan Motivasi Belajar Siswa dalam Pembelajaran Pendidikan Agama Islam - Masnadi, Masnadi; Pranajaya, Syatria Adymas; Mahmud, Salami (FITRAH: International Islamic Education Journal, 2024)
This study aims to analyze the factors influencing student learning motivation in Islamic Religious Education (IRE) and formulate strategies for improving motivation that can be applied in the context of IRE teaching in schools. Using a library research approach, this study reviews various literature on learning motivation theories and their application in IRE teaching. The findings indicate that student learning motivation is influenced by internal factors, such as self-efficacy and interest in the subject matter, as well as external factors, including social support from teachers, parents, and peers. The application of learning strategies that are relevant to students' life experiences and the use of educational technology has proven effective in enhancing student learning motivation in IRE. Furthermore, learning approaches that emphasize student active involvement and allow them to find personal meaning in religious materials have proven to be more effective in increasing their motivation. The integration of intrinsic and extrinsic motivation in a balanced way can enhance the meaningfulness of IRE learning, which, in turn, improves students' understanding and practice of religious teachings in their daily lives. Abstrak Penelitian ini bertujuan untuk menganalisis faktor-faktor yang mempengaruhi motivasi belajar siswa dalam pembelajaran Pendidikan Agama Islam (PAI) dan merumuskan strategi peningkatan motivasi yang dapat diterapkan dalam konteks pembelajaran PAI di sekolah. Dengan menggunakan pendekatan kajian pustaka (library research), penelitian ini menganalisis berbagai literatur tentang teori motivasi belajar dan penerapannya dalam pembelajaran PAI. Hasil penelitian menunjukkan bahwa motivasi belajar siswa dipengaruhi oleh faktor internal, seperti keyakinan diri (self-efficacy) dan minat terhadap materi, serta faktor eksternal, seperti dukungan sosial dari guru, orang tua, dan teman sebaya. Penerapan strategi pembelajaran yang relevan dengan kehidupan siswa dan pemanfaatan teknologi pendidikan terbukti efektif dalam meningkatkan motivasi belajar siswa dalam pembelajaran PAI. Selain itu, pembelajaran yang mengedepankan keterlibatan aktif siswa serta memungkinkan mereka menemukan makna dalam materi agama terbukti lebih efektif dalam meningkatkan motivasi belajar mereka. Pengintegrasian motivasi intrinsik dan ekstrinsik secara seimbang dapat meningkatkan kebermaknaan pembelajaran PAI, yang pada gilirannya dapat memperbaiki pemahaman dan pengamalan ajaran agama dalam kehidupan sehari-hari siswa.